Managing network goals: The interplay of network and firm levels - Gerrit W. Ziggers; Taras Gagalyuk; Jon Hanf (Proceedings in system dynamics and innovation in food networks 2010, 2010)
This article provides several contributions to the general understanding of governance in networks and the achievement of private and common goals. A simple, integrated framework for understanding why firms collaborate and under which conditions they establish durable networks that succeed in achieving goals is provided. Network theory is extended by explicitly distinguishing between dyadic-level governance and network-level governance conditions, and by identifying exchange conditions that promote governance.This way issues as how networks evolve, how they are governed, and ultimately, how collective outcomes might be generated can be better comprehended. This is especially relevant to policy planners and those having a perspective that goes beyond the performance of individual organizations.
Keywords: 330